Contrasting Phylogeographic Patterns in Lumnitzera Mangroves Across the Indo-West Pacific - Guo, Wuxia; Banerjee, Achyut Kumar; Wu, Haidan; Ng, Wei Lun; Feng, Hui; Qiao, Sitan; Liu, Ying; Huang, Yelin (Frontiers in Plant Science, 2021)
Mangroves are ecologically important forest communities in tropical and subtropical coasts, the effective management of which requires understanding of their phylogeographic patterns. However, these patterns often vary among different species, even among ecologically similar taxa or congeneric species. Here, we investigated the levels and patterns of genetic variation within Lumnitzera consisting of two species (L. racemosa and L. littorea) with nearly sympatric ranges across the Indo-West Pacific region (IWP) by sequencing three chloroplast DNA regions (for both species) and genotyping 11 nuclear microsatellite loci (for L. littorea). Consistent with findings in studies on other mangrove species, we found that both L. racemosa and L. littorea showed relatively high genetic variation among populations but low genetic variation within populations. Haplotype network and genetic clustering analyses indicated two well differentiated clades in both L. racemosa and L. littorea. The relationship between geographic and genetic distances and divergence time estimates of the haplotypes indicated that limited dispersal ability of the propagules, emergence of land barriers during ancient sea-level changes and contemporary oceanic circulation pattern in the IWP influenced the current population structure of the two species. However, the position of genetic break was found to vary between the two species: in L. racemosa, strong divergence was observed between populations from the Indian Ocean and the Pacific Ocean possibly due to land barrier effect of the Malay Peninsula; in L. littorea, the phylogeographic pattern was created by a more eastward genetic break along the biogeographic barrier identified as the Huxley’s line. Overall, our findings strongly supported previous hypothesis of mangrove species divergence and revealed that the two Lumnitzera species have different phylogeographic patterns despite their close genetic relationship and similar current geographic distribution. The findings also provided references for the management of Lumnitzera mangroves, especially for the threatened L. littorea.